A broadly applicable [18F]trifluoromethylation of aryl and heteroaryl iodides for PET imaging. - Huiban, M; Tredwell, M; Mizuta, S; Wan, Z; Zhang, X; Collier, T; Gouverneur, V; Passchier, J (2013)
Molecules labelled with the unnatural isotope fluorine-18 are used for positron emission tomography. Currently, this molecular imaging technology is not exploited at its full potential because many (18)F-labelled probes are inaccessible or notoriously difficult to produce. Typical challenges associated with (18)F radiochemistry are the short half-life of (18)F (<2 h), the use of sub-stoichiometric amounts of (18)F, relative to the precursor and other reagents, as well as the limited availability of parent (18)F sources of suitable reactivity ([(18)F]F(-) and [(18)F]F2). There is a high-priority demand for general methods allowing access to [(18)F]CF3-substituted molecules for application in pharmaceutical discovery programmes. We report the development of a process for the late-stage [(18)F]trifluoromethylation of (hetero)arenes from [(18)F]fluoride using commercially available reagents and (hetero)aryl iodides. This [(18)F]CuCF3-based protocol benefits from a large substrate scope and is characterized by its operational simplicity.